3Dscript: animating 3D/4D microscopy data using a naturallanguage- based syntax. - Palmisano, Ralf; Tripal, Philipp; Schmid, Benjamin; Fraaß, Tina (https://www.quantitativebioimaging.com/qbi2020/conference-and-program-booklet/, 2020)
We introduce a software framework that assembles 3D animations of imaging data using a textual description with a syntax based on natural English language. In contrast to the established key frame based approach, smooth and complex motion sequences are intuitively implemented by concatenating multiple instructions. [1] The syntax is extensible and we demonstrate its integration into existing 3D visualization software. The user typically stores different rendering settings and scene transformations in a number of key frames along a timeline, and the rendering engine creates a smooth animation by interpolating between them. Key frames save the spatial transformation of an object as a state, e.g. three angles for a rotation, and not as a transition. This at least 4 key frames are required to define a 360- degree rotation with constant speed unambiguously. Even more are required if the motion is non-linear, which is essential for achieving smooth and pleasant motions. Software packages therefore typically provide a shortcut to insert key frames for rotations around common axes. More complex motions such as combined rotations around multiple axes, however, are difficult to achieve. The syntax based on natural English language maximizes experience and provides easy access for users of distinct fields. Each instruction is an English sentence. Complex motion sequences are implemented by combining multiple instructions which are applied in the order they appear in the text. The syntax comprises phrases for standard non-linear accelerations, resulting in smooth and natural animations. Self-defined macro functions can be used to define motion and other parameters as functions over time. We provide 3DScript as a Fiji/ImageJ plugin including an hardware-accelerated 3D renderer and a dedicated editor featuring auto-completion and recording. Although tailored to the included rendering engine, both the syntax and our animation framework can be easily adapted by other rendering software.<br
Keywords: 3D Animation; Natural Language Syntax; 3Dscript; Fiji/ImageJ Plug-In